Assessment of Bone Mineral Density in Chronic Obstructive Pulmonary Disease Patients (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background:  Main co-morbidities of chronic obstructive pulmonary disease that restricts physical exercise is osteoporosis. In this study we assess chronic obstructive pulmonary disease patients  for osteoporosis, osteopenia and determine correlation of body mass index, number of pack years, severity of chronic obstructive pulmonary disease with bone mineral densityMethod and patients:This cross-sectional study was carried out on 61 chronic obstructive pulmonary disease patients.. Dual energy x-ray absorptiometry was used to evaluate the bone mineral densities at lumbar spine. According to WHO guidelines, patients with a T score greater than -1 were classified as having normal bone density, those with a T score of (-1 )to (-2) as having osteopenia, and those with a T score of less than -2.5 as having osteoporotic bone density.Results:Sixty -  one chronic obstructive pulmonary disease patients were included in this study, 11 patients (18%) had normal bone mineral density, fifty patients had abnormal bone mineral density .Also thirty - two patients had osteoporosis(52.5%) and 18 (29.5%) had osteopenia. .BMD correlated directly with BMI (P value=0.009) and inversely with  number of pack years (P = 0.000), ,BMD correlated inversely with severity of COPD  (P = 0.001) .Conclusion:Patients with chronic obstructive lung disease had a higher chance of osteoporotic fractures and decreased bone mineral density.A lower BMI, more pack years, and a rise in the severity of the condition raised chance of osteoporosis..